Bone mass and bone turnover in premenopausal women with fibromyalgia syndrome - Gürbüz, Ali; Kaya, Arzu; Balcı, Tansel Ansal (My University, 2018)
In this study, we aimed to compare osteoporosis (OP)-related bone mineral density, and bone turnover (markers of formation, and resorption) between patients with Fibromyalgia Syndrome (FMS) and degenerative disc disease, and to determine the relationship of these parameters with clinical, functional and emotional evaluation outcomes in FMS. Fifty premenopausal women with FMS and 50 premenopausal female control patients with degenerative disc disease were enrolled. The patient and physician’s global assessment of disease were assessed on a visual analog scale (VAS). Disease severity was determined with the Fibromyalgia Impact Questionnaire (FIQ). For the evaluation of fatigue The Modified Fatigue Impact Scale (MFIS) and Fatigue Severity Scale (FSS) were used. The quality of life of all patients was evaluated using Nottingham Health Profile (NHP), Oswestry Disability Index (ODI), and QUALEFFO-41. The emotional state of all patients with chronic pain was evaluated with Hospital Anxiety and Depression Scale (HADS). Bone turnover markers [serum bone-specific alkaline phosphatase (bALP) and serum osteocalcin as markers of bone formation, serum â-isomerized Carboxy-terminal telopeptide of collagen type I (â-CTX) and urine hydroxyproline (OH-Pro) as markers of bone resorption], serum parathyroid hormone (PTH) and 25-hydroxyvitamin D [25(OH)D] levels, lumbar spine and left proximal femur bone mineral density (BMD) and T scores were measured in both groups. The FIQ, MFIS, FSS, NHP, ODI, QUALEFFO-41, HADS-A and HADS-D scores were statistically significantly higher in the FMS group relative to the patient control group. A significant difference between FMS and patient control group as for bone formation (bALP and osteocalcin) and resorption (â-CTX ve OH-Pro) markers was not detected. In the FMS group lumbar spine and left proximal femur BMD and T score values were significantly lower when compared with the patient control group. In the FMS group significant correlations were found between serum 25(OH)D and â-CTX values and VAS scores evaluated by the patient and physician, SS scale, FIQ, MFIS, ODI, QUALEFFO-41 and NHP scores. In conclusion many factors including depression and anxiety attacks, the presence of widespread pain and a decline in physical activity level and quality of life in FMS patients make them more prone to osteoporosis. In patients with FMS, osteoporosis is a major cause of morbidity and should not be neglected.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp